Witnessing Hope in the Long Learning of Solidarity: The Intersection of Hope and Learning in the Remembered Experiences of Canadian Solidarity Activists - Janice Acton (Adult Education Research Conference, 2004)
Hope, while largely invisible, is profoundly present in transformative learning in social movements. It is valuable for activists to reflect back through the lens of hope on what they witnessed in the past as being “possible” to help them affirm and augment a new sense of meaning and hope today.